Embedding and Positioning of Two Fe(II) (4)L(4) Cages in Supramolecular Tripeptide Gels for Selective Chemical Segregation - Kieffer, Marion (Angew Chem Int Ed Engl, 2019)
An unreported d,l‐tripeptide self‐assembled into gels that embedded Fe(II) (4)L(4) metal–organic cages to form materials that were characterized by TEM, EDX, Raman spectroscopy, rheometry, UV/Vis and NMR spectroscopy, and circular dichroism. The cage type and concentration modulated gel viscoelasticity, and thus the diffusion rate of molecular guests through the nanostructured matrix, as gauged by (19)F and (1)H NMR spectroscopy. When two different cages were added to spatially separated gel layers, the gel–cage composite material enabled the spatial segregation of a mixture of guests that diffused into the gel. Each cage selectively encapsulated its preferred guest during diffusion. We thus present a new strategy for using nested supramolecular interactions to enable the separation of small molecules.